Wound healing by transplantation of mesenchymal stromal cells loaded on polyethylene terephthalate scaffold: Implications for skin injury treatment. Issue 4 (April 2023) - Pereira, Betzabeth; Duque, Kharelys; Ramos-Gonzalez, Giselle; Díaz-Solano, Dylana; Wittig, Olga; Zamora, Mariela; Gledhill, Teresa; Cardier, José E.
Highlights: Cutaneous wound healing continues being a serious medical problem. Cell therapy based on mesenchymal stromal cells (MSC) has emerged as a promising therapeutic alternative to treat skin wounds. Here we show that MSCs loaded on polyethylene terephthalate (PET) scaffold induce a rapid re-epithelialization of cutaneous wounds. Abstract: Background: Several clinical studies have shown that cellular therapy based on mesenchymal stromal cells (MSCs) transplantation may accelerate wound healing. One major challenge is the delivery system used for MSCs transplantation. In this work, we evaluated the capacity of a scaffold based on polyethylene terephthalate (PET) to maintain the viability and biological functions of MSCs, in vitro . We examined the capacity of MSCs loaded on PET (MSCs/PET) to induce wound healing in an experimental model of full-thickness wound. Methods: Human MSCs were seeded and cultured on PET membranes at 37 °C for 48 h. Adhesion, viability, proliferation, migration, multipotential differentiation and chemokine production were evaluated in cultures of MSCs/PET. The possible therapeutic effect of MSCs/PET on the re-epithelialization of full thickness wounds was examined at day 3 post-wounding in C57BL/6 mice. Histological and immunohistochemical (IH) studies were performed to evaluate wound re-epithelialization and the presence of epithelial progenitor cells (EPC). As controls, wounds without treatment or treated with PET were established. Results: We observed MSCs adhered to PET membranes and maintained their viability, proliferation and migration. They preserved their multipotential capacity of differentiation and ability of chemokine production. MSCs/PET implants promoted an accelerated wound re-epithelialization, after three days post-wounding. It was associated with the presence of EPC Lgr6 + and K6 + . Discussion: Our results show that MSCs/PET implants induce a rapid re-epithelialization of deep- and full-thickness wounds. MSCs/PET implants constitute a potential clinical therapy for treating cutaneous wounds.